Examining the Impact of Telehealth Visits on Patient and Family Experience in a Pediatric Emergency and Urgent Care Center - Abigail Gauthier; Callie Krentz; Shiran Chan; Michelle Widecan; Adam Vukovic (Patient Experience Journal)
Providers and healthcare organizations have created novel ways of evaluating patients using telehealth. Patient volumes in urgent cares (UCs) and emergency departments (EDs) continue to climb, contributing to longer wait times and suboptimal patient and family experiences (PFEs). Optimizing use of telehealth may not only impact PFE of those evaluated virtually, but also reduce crowding in EDs and UCs, indirectly impacting PFE in those spaces as well. The purpose of this study is to identify any association between telehealth encounters and PFE scores. This is a retrospective review of patients seen via telehealth in virtual urgent care, UC, or the ED who completed a post-visit PFE survey. Data were extracted from our electronic health record and our experience survey platform. We generated descriptive statistics of our patient populations seeking care at all three site categories who were treated for specific diagnoses. We performed univariate and multivariate analysis to identify independent associations between encounter characteristics and PFE scores. While encounter location was not independently associated with PFE scores, the interaction between wait time and location of service favors use of telehealth services for low-acuity patients by improving the healthcare experience for these patients and families.